Quotation and inclusion in the poetry of Ahmed Shalabi Rhetorical Stylistic study - Hawez, Zhala J. (Mitanni Journal of Humanitarian Sciences, 2023)
Research objective: The research aims to demonstrate the importance of the overlap and interaction of quotation and implication by producing a functional significance in order to serve the meaning, and to communicate it in a way that is able to persuade and influence the recipient. In addition, interdependence in terms of pronunciation, and the coalition in terms of meaning. The difficulty of the research: lies in the fact that the poet (Shalabi) - as far as we know - has never dealt with his poetic output in a book before, but rather it is separate articles in some magazines and newspapers, and this may be due to the fact that the poet is hidden from many of the polite people in our literary world due to the lack of care for writers The regions, where the poet's residence far from the capital led to something obscuring him from the limelight and fame, despite the originality of his talent and the novelty of his productions, which caused him a lot of injustice, so he did not get his due appreciation. Research methodology: In this research, we followed this analytical descriptive approach by revealing the deep semantic meanings by stating the effect of quotation and implication that the meaning carried, and by which the apparent meaning went beyond the deep meaning, and how the poet employed the overlapping of the quoted and embedded text in highlighting the meaning, and revealing his intent. Structuring the research: We distributed the scientific material for the research into two sections: the first topic consists of two requirements, so the first requirement came to tell us about the poet (Ahmed Shalaby), his life and upbringing, the factors of his poetics, his literary and scientific effects, and the opinions of critics in his poetry, and the second requirement about quotation and implication: language and idiomatically. As for the second topic, in quotation and implication in the poetry of (Ahmed Shalaby), it consists of three demands: the first in religious quotation, the second in poetic implication, and the third in historical implication, in addition to mentioning the most important conclusions and recommendations that we reached, and a summary in both languages. Kurdish and English.